Schinus terebinthifolius Raddi: a literature review associated with an in silico study (Research, Society and Development, 2022)
The present work gathered studies in the literature about the biological activities of Schinus terebinthifolius and evaluated possible physicochemical, pharmacokinetic, and toxicity characteristics of molecules isolated from this species. Initially, a broad literature review was conducted using the following databases: Google Scholar, Portal de Periódicos Capes, SciELO and PubMed, with the descriptors: "Schinus terebinthifolius Raddi", "pharmacological properties", "isolated compounds", including studies published in Portuguese and English between the years 2001 and• The selected molecules were designed in MarvinSketch software and submitted to PreADMET and Protox II software. Regarding the biological studies, the literature revealed that S. terebinthifolius has the activities: anti-inflammatory, wound healing, anti-ulcer, antibacterial, antifungal, antioxidant, antihistaminic, larvicidal, insecticidal, and repellent. The chemical studies showed that S. terebinthifolius has a significant amount of terpenes, especially monoterpenes and sesquiterpenes. The following molecules were selected: limonene, α-pinene, β-pinene, α-felandrene, δ-3-carene, germacrene D, myrcene, and o-cymene. The literature concerning S. terebinthifolius demonstrates how this plant has an extensive framework of activities. It was observed that the molecules presented advantages and disadvantages in physicochemical, pharmacokinetic and toxicological parameters. In general, all molecules followed Lipinski's rule, and all molecules were toxic to algae, Medaka and hERG, whereas immunotoxicity was only positive for myrcene. Considering the regular performance in the other parameters, and the low inhibitory potential for CYP's, the most promising molecules are α-pinene and δ-3-carene. However, further toxicity studies are important.